2021
DOI: 10.1155/2021/8886085
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Helicobacter pylori Infection of the Gallbladder and Chronic Cholecystitis and Cholelithiasis: A Systematic Review and Meta-Analysis

Abstract: Helicobacter pylori (H. pylori) is proved to be the main pathogenic agent of various diseases, including chronic gastritis, gastric ulcer, duodenal ulcer, and gastric cancer. In addition, chronic cholecystitis and cholelithiasis are common worldwide, which are supposed to increase the total mortality of patients. Epidemiologic evidence on the relationship between H. pylori infection of the gallbladder and chronic cholecystitis/cholelithiasis still remains unclear. We conducted a systematic review and meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Among those having H. pylori majority were females. (p=0.23) similar results were found by Liang Wang et al [11] where they showed that female gender was not statistically significant. In Our study No statistical significance was seen between H. pylori and type of stone.…”
Section: Association Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Among those having H. pylori majority were females. (p=0.23) similar results were found by Liang Wang et al [11] where they showed that female gender was not statistically significant. In Our study No statistical significance was seen between H. pylori and type of stone.…”
Section: Association Resultssupporting
confidence: 84%
“…Data analysis was done using and open epi version 2.3.1. [11] showed that risk of gallstone diseases increases with age in all racial groups. Because of female sex hormones and increased cholesterol secretion, females with obesity are more likely to get gallstones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute cholecystitis is the most frequent complication of symptomatic gallstone disease and in 90% of cases is caused by occlusion of the cystic duct, though the neck of the gallbladder may also be occluded [ 17 , 18 ]. Occlusion is usually accompanied by inflammation that in some cases may be bacterial [ 19 ], particularly with H. pylori [ 20 ]. The characteristic sharp continuous pain of symptomatic cholelithiasis is known as biliary colic (BC).…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…After 70 years, gender differences in incidence disappear, the incidence gradually increases and reaches 30-40 %. Publications of clinical observations of foreign and domestic literature indicate that in the last 45-50 years the incidence of cholecystitis doubles every 10 years, and the clinic is characterized by diversity and atypical course [17][18][19][20][21][22][23]. Ultrasound showed a fairly high diagnostic capability in the diagnosis of cholecystitis.…”
Section: Introductionmentioning
confidence: 99%